Varga Zsigmond teológia professzor, a Debreceni m. kir. Tisza István-Tudományegyetem 1932/33. évi Rector Magnificusa - Baráth, Levente (Gerundium, 2018)
Zsigmond Varga, Professor of the History of Religion, the Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen during the academic year 1933/1934. Several memorable events took place at the university during his time in office. The historical background of this was the fact that the political and social tensions caused by restrictive measures taken by the Hungarian government to fight the consequences of the Great Depression reached their peak in that academic year. There were several events that made the extraordinary actions of rector Zsigmond Varga necessary: the public debate on the policy of education aiming at the restructuring of the higher education threatened the university with loosing one of its four faculties and the ongoing student revolts hindered the teaching and research activities for months. In addition to Varga’s activity in the University administration, this study describes his work as an academic and as a scholar, and addresses his public activities outside of the university, too. It also offers a glimpse into his family life at a certain point of time. Referring to a memorial booklet written by Varga, his son, Zsigmond Varga jr., the young Reformed minister and promising biblical scholar is also remembered in this study. Varga jr. was a student of the University of Vienna, he was nprisoned by the Gestapo and he died a martyr’s death in the concentration camp of Mauthausen-Gusen.